PENELITIAN BERBAGAI JENIS KAYU LIMBAH PENGOLAHAN UNTUK PEMILIHAN BAHAN BAKU BRIKET ARANG - Malik, Usman (Edu Research, 2012)
The waste of timber industry can be utilized to produce some valuable products. A research had been conducted to study such possibility. The research was to study the conversion of wood into charcoal briquetting using adhesive or heatingprocess. Result showed that the heating value of charcoal briquetting made from kempas wood (koompassia malaccensis maing), meranti (shorea spp.) and pulai (alstonia spp) increases significantly compared to that of raw material. The product made from kempas wood (koompassia malaccensismaing.) was formed to have the highest energy per cc (density) followed by those of made of meranti (shorea spp.), ramin (gonystylus bancanus kurz.). However, raw material availability must be consideret in establishing charcoal briquetting industry.